Chronicles from the land of the happiest people on earth - Sonyinka, Wolf. (New York Pantheon Books, 2021)
A towering figure in world literature gives us a tour de force, his first novel in nearly one-half century: a savagely satiric, gleefully irreverent, rollicking, fictional meditation on how power and greed can corrupt the soul of a nation. ("You don't see things the same way when you encounter a voice like that."-Toni Morrison) In an imaginary Nigeria, a cunning entrepreneur is selling body parts stolen from Dr. Menka's hospital for use in ritualistic practices. Dr. Menka shares the grisly news with his oldest college friend, bon viveur, star engineer, and Yoruba royal, Duyole Pitan-Payne-the life of every party- who is about to assume a prestigious post at the United Nations in New York. It now seems that someone is determined that he not make it there. Neither Dr. Menka nor Duyole knows why, or how close the enemy is, how powerful. Chronicles from the Land of the Happiest People on Earth is at once a literary hoot, a crafty whodunit, and a scathing indictment of Nigeria's political elite. It is a stirring call to arms against the abuse of power from one of that country's fiercest political activists, who just happens to be a global literary giant
Includes index
Keywords: Sale of organs, tissues, etc.--Nigeria--Fiction.